PENGARUH KECERDESAN EMOSIONAL DAN MOTIVASI TERHADAP KINERJA TENAGA KEPENDIDIKAN PADA FAKULTAS KEDOKTERAN DAN KESEHATAN UNIVERSITAS MUHAMMADIYAH JAKARTA - Irawan, Dani; Hasan, Diana (Taksasila Edukasi Insani, 2026)
This study aims to examine and analyze the influence of emotional intellegence and motivation to employee performance.The method in collecting data in this study was conducted by distributing questionnaires to 57 employee educatinal staff faculty od medicine and health muhammadiyah university of jakarta. The research method used is quantitative method which is associative by using primary data.The result of study indicate that emotion intellegence has a positive and significant effect on employee performance with t count values of 6,893 2,00 and significant 0,000 0,05, motivation has a positive and significant effect on employee performance with a value of t count of 2,526 2,00 and significant 0,001 0,05. Together emotional intellegence and motivation have a positive and significant effect on employee performance with an F value of 58,731 3,16 and a significant value 0,000 0,05.Keywords : Emotion Intellegence, Motivation, Employee Performance